A bioética no ensino médio: um caminho para a reflexão de práticas de humanização do sujeito - Gomes, Pedro Braga (2010)
This study focuses on the presence of bioethics as subject of the discipline of Philosophy for High School through the implementation of the curriculum proposal the Secretary of State for Education of São Paulo, 2008. The study is proposed as a hypothesis that the presence of Bioethics in the curriculum of the State of São Paulo is a way of educating for responsibility in the wake of social revolution and biotechnology, highlights the need for ethical standards in relation to life, not to convert human life into a commodity in the hands of scientists or economic groups. From a documentary study seeks to discuss the proposed curriculum implemented in the state system of public education St. Paul in 2008, based on the content of Bioethical principles in the discipline of philosophy, from the theoretical basis of Dussel (2002), Freire (1994, 1996) and Heidegger (2000). It adopts the hermeneutic approach to this study in view of Gadamer (1999), we seek to interpret the meanings expressed or implied in the document, the construction of meaning from inferences. The study indicates that the presence of Bioethics contributes to the reflection of the subject (Bio) ethics, as being a person and be subject, revealing how the care value in the way of teaching responsibility